2012
DOI: 10.3109/17453674.2012.678802
|View full text |Cite
|
Sign up to set email alerts
|

Physeal growth arrest after tibial lengthening in achondroplasia

Abstract: Background and purposeBilateral tibial lengthening has become one of the standard treatments for upper segment-lower segment disproportion and to improve quality of life in achondroplasia. We determined the effect of tibial lengthening on the tibial physis and compared tibial growth that occurred at the physis with that in non-operated patients with acondroplasia.MethodsWe performed a retrospective analysis of serial radiographs until skeletal maturity in 23 achondroplasia patients who underwent bilateral tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They showed that continuous compressive forces on the physis result in either temporary or permanent cessation of growth according to the Heuter-Volkmann principle. Sang-Heaon et al in their study showed the growth arrest on the tibia, especially on the medial portion of the proximal physis [22]. They also suggested starting lengthening in achondroplasia patients after 11 years old in their population when the growth of proximal tibia physeal decrease to less than 10 mm/years.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They showed that continuous compressive forces on the physis result in either temporary or permanent cessation of growth according to the Heuter-Volkmann principle. Sang-Heaon et al in their study showed the growth arrest on the tibia, especially on the medial portion of the proximal physis [22]. They also suggested starting lengthening in achondroplasia patients after 11 years old in their population when the growth of proximal tibia physeal decrease to less than 10 mm/years.…”
Section: Discussionmentioning
confidence: 91%
“…Sang-Heaon et al . in their study showed the growth arrest on the tibia, especially on the medial portion of the proximal physis [22]. They also suggested starting lengthening in achondroplasia patients after 11 years old in their population when the growth of proximal tibia physeal decrease to less than 10 mm/years.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 58 included studies, four were randomised control trials [ 22 , 32 , 53 , 54 ], 25 were retrospective case studies [ 5 , 23 25 , 27 , 28 , 30 , 34 , 35 , 39 , 41 , 42 , 45 , 46 , 48 , 49 , 57 , 59 , 65 69 , 71 , 73 ], 15 were retrospective cohort studies [ 20 , 21 , 26 , 29 , 31 , 36 , 38 , 40 , 47 , 55 , 58 , 60 , 61 , 70 , 74 ], eight were controlled before and after studies [ 15 , 51 , 52 , 56 , 62 64 , 72 ], two were prognostic studies [ 19 , 37 ], and one study was a non-randomised control trial [ 50 ]. There were three cross-sectional studies that used patient focused surveys [ 33 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increased height and longer arms may also reduce some of the limitations in mobility, activities of daily living, and independence that have been reported for adults with achondroplasia [ 3 , 24 ]. Furthermore, improvements in growth may reduce the need for surgical lengthening of lower and upper limbs, which together can take several years to complete [ 29 , 30 ] and may have a substantial negative impact on the patient’s HRQoL during that period.…”
Section: Discussionmentioning
confidence: 99%